Metrosexual: Emerging and Lucrative Segment for Marketers - Bano, Sobia; Sharif, Md Akhir Mohd (International Review of Management and Marketing, 2016)
Metrosexual is a phenomenon of 21st century, which has challenged the traditional masculinity. Metrosexual is an affluent urban male, who spends a lot of their income on personal grooming. They are concerned about their appearance and are aware of all latest trends and fashion. The footprints of this sub-culture are evident around the globe. The growing sales of male grooming products are the indicators that how the traditional notion of men’s identity is changing. This is a time where companies are spending money to cater the needs of the growing demand of male. This paper is a little endeavor to discuss the changing values of the society and the growing phenomena of metrosexual. The paper will discuss roots of masculinity and femininity, its development and the blurring of gender roles. Based on literature and published reports paper will discuss the various statistics related to sales and the increase of male grooming consumption around the globe. At the end paper will discuss that how metrosexual is a lucrative segment as the market of male grooming products is showing positive trend and as man has more disposable income. Keywords: metrosexual, gender, male grooming, cosmetics JEL Classifications: M16, M30, M31, M37